Effective group therapies for young adults affected by cancer : using support groups in clinical settings in the US - Kurker, Sarah ([S.l.] : Routledge, 2021)
Outlining the unique psychosocial and development issues faced by young adults affected by cancer, this text draws on qualitative data from two pilot studies conducted in the United States to illustrate how the needs of this often-overlooked population can be effectively met via group therapy in clinical settings. Drawing on 25 years of experience as a licensed clinical social worker supporting pediatric and young adult cancer patients and their families, Kurker focuses on the role of the clinician in structuring support group sessions. Chapters draw on patient perspectives to demonstrate effective application of interventions to help adolescents work through trauma associated with a diagnosis of cancer, treatment, recovery and the impacts on their development. Outcomes from these studies also include strategies for selecting support group participants, structuring group activities and securing funding. Effective Group Therapies for Young Adults Affected by Cancer will be a valuable text for oncology social workers and clinicians involved in adolescent support services. In addition, researchers and postgraduate students with an interest in the fields of social work, psychology and adolescent development will find the book of interest.
OCLC-licensed vendor bibliographic record.
Keywords: Cancer in adolescence; Group counseling; Young adults -- Services for; Young adults -- Mental health; Cancer -- Patients -- Services for; Cancer -- Patients -- Mental health; SOCIAL SCIENCE / Social Work; PSYCHOLOGY / Developmental / Adolescent; PSYCHOLOGY / Mental Health